PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING TERHADAP HASIL BELAJAR SISWA PADA KONSEP SALING KETERGANTUNGAN DALAM EKOSISTEM DI KELAS VII SMP NEGERI 18 PEKANBARU TAHUN AJARAN 2014 / 2015 - Jumiati Jumiati (Lectura : Jurnal Pendidikan, 2015)
The aim of this research was to find out the effect of cooperative learning type snowballthrowing to improve student learning achievement on the reliance mutualin in theecosystem concept. The research was conducted at SMP Negeri 18 Pekanbaru at firstsemester in academic years 2014 / 2015. Design of the research was quasi-experimental,The Matching Only Pretest – Posttest Control Group Design. Sample of the research wastaken two classes with the number of students in each 40 people who were taken by usingsimple random sampling technique. The data were collected by using pretest, posttest andteacher’s and students’ activities observation sheets. The data analysis technique used inthis research was 2 sample independent t test, if the data were normal and homogen. Themean N-gain experimental class was 0.72 high category and the control class was 0.44medium category. Based on the result of statistical test that there were significantdifferences between the mean N-Gain experimental class and control class. Thereby canbe conluded that there were significant application of cooperative learning type snowballthrowing to improve student learning achievement on the reliance mutualin in theecosystem concept class VII SMPN 18 pekanbaru academic year 2014 / 2015.